The Influence of Servqual and Technology Acceptance Model on Maxim Customer Satisfaction - Achmad Fazi Alam; Dhany Isnaeni Dharmawan (Universitas Serang Raya, 2025)
The increasingly advanced and modern social and cultural development of society has led many people to prefer instant and practical things, such as online transportation. Digital technology has changed people's consumption patterns, including in the transportation industry. This study aims to analyze the influence of SERVQUAL and the Technology Acceptance Model (TAM) on maximizing customer satisfaction. The research employed a quantitative approach, distributing questionnaires to 400 respondents who were Maxim app users. Data analysis was performed using SPSS version 25, including validity and reliability tests, as well as multiple linear regression and path analysis. The results showed that Service Quality, Perceived Usefulness, and Perceived Ease of Use had a significant effect on Customer Satisfaction. Furthermore, Customer Satisfaction also significantly influences the intention to use. Directly, Perceived Usefulness and Service Quality were found to significantly influence Behavior intention to use, while perceived ease of use only significantly influenced behavior intention to use when mediated by customer satisfaction. These findings highlight the significance of service quality, perceived usefulness, and perceived ease of use in fostering customer satisfaction and loyalty among Maxim users.